Dual inhibition of tumour necrosis factor and interleukin-17A with ABT-122: open-label long-term extension studies in rheumatoid arthritis or psoriatic arthritis. (18th July 2018) - Genovese, Mark C; Weinblatt, Michael E; Mease, Philip J; Aelion, Jacob A; Peloso, Paul M; Chen, Kun; Li, Yihan; Liu, John; Othman, Ahmed A; Khatri, Amit; Mansikka, Heikki T; Leszczyński, Piotr
Abstract: Objectives: To evaluate the safety and maintenance of efficacy with ABT-122, a bi-specific monoclonal antibody targeting TNF and IL-17A, in patients with RA or PsA in open-label, 24-week extensions [open-label extensions (OLEs)] of 12-week, randomized, double-blind studies. Methods: All patients received ABT-122 (RA, 120 mg; PsA, 240 mg) subcutaneously every other week on background MTX. Safety assessments included adverse events (AEs) and laboratory parameters. Efficacy was evaluated with ACR responses, 28-joint DAS using high-sensitivity CRP [DAS28 (hsCRP)], and Psoriasis Area and Severity Index (PsA study). Results: The RA OLE study enrolled 158 patients; the PsA OLE study enrolled 168 patients. In the RA OLE study, the incidence of treatment emergent AEs (TEAEs; 41%) appeared similar to the double-blind study (36–43%). In the PsA OLE study, 57% of patients reported ⩾1 TEAE (double-blind study, 42–53%). Most TEAEs were mild or moderate in severity. There were no neutrophil abnormalities greater than grade 2. Grade 3 and/or 4 laboratory abnormalities were reported for lymphocytes, alanine aminotransferase, aspartate aminotransferase, bilirubin and haemoglobin; the number of these severe laboratory values was low (0.6–3.0%), except grade 3 lymphocyte count decreased (11.5%) in the RA study. In both OLE studies, efficacy assessed by ACR responses and other disease activity scores was maintained over the 24 weeks. Conclusion: ABT-122 demonstrated acceptable tolerability and maintenance of efficacy for up to 36 weeks in patients with RA or PsA receiving background MTX. Trial registration: ClinicalTrials.gov, http://clinicaltrials.gov, NCT02433340 and NCT02429895